Exercise associated with γ-oryzanol supplementation suppresses oxidative stress and prevents changes in locomotion in Drosophila melanogaster. (1st February 2021) - Dahleh, Mustafa Munir Mustafa; Araujo, Stífani Machado; Bortolotto, Vandreza Cardoso; Pinheiro, Franciane Cabral; Poetini, Márcia Rósula; Musachio, Elize Aparecida Santos; Meichtry, Luana Barreto; Couto, Shanda de Freitas; Prigol, Marina
Abstract: Association to early mortality and sedentarism was already demonstrated in the literature; nevertheless, some possible biochemical mechanisms around physical inactivity still need answers. The use of an invertebrate model, such as Drosophila melanogaster, can reproduce reliable responses in inducing an exercise protocol with exogenous antioxidant supplementation. This study main evaluates the effect of exercise (EXE) associated with γ-oryzanol (ORY) supplementation to improve locomotor behavior, antioxidant defenses, and survival in Drosophila melanogaster . Two-day old flies were submitted to a protocol for seven days, divided into five groups: Control, Movement-Limited Flies (MLF), EXE, ORY [25  µM], and EXE + ORY [25  µM]. The survival rate was evaluated, followed by open field and negative geotaxis. Flies were euthanized and subjected to analysis for acetylcholinesterase (AChE) and antioxidant enzymes activity, glycidic and lipid parameters, body weight, reactive species (RS), and lipid peroxidation. EXE and EXE + ORY flies showed increased survival and locomotor activity, improved glycidic and lipid parameters, with a lower RS production, and increased antioxidant defenses compared to Control, and EXE + ORY when compared to the EXE group, obtained an increase in the ratio of protein levels/body weight, decreased ratio of triglyceride levels/body weight and decreased lipid peroxidation. However, MLF showed less survival and decreased locomotor activity, possibly due to increased AChE activity and reduced antioxidant defenses. The EXE and EXE + ORY demonstrate effective results in maintaining endogenous defenses, with increased locomotor activity, supporting evidence on EXE benefits, and supplementation with antioxidant compounds face of health paradigms. Highlights: New protocol system of exercise on Drosophila melanogaster model. ORY demonstrates synergistic effect with EXE. Exercise with ORY supplementation increases locomotor behavior. Exercise with ORY supplementation decrease oxidative damages on flies. Graphical Abstract: UF0001